2004
DOI: 10.1073/pnas.0401407101
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic studies of roquefortine C: Synthesis of isoroquefortine C and a heterocycle

Abstract: The syntheses of isoroquefortine C and a related heterocycle were achieved by implementation of both intra-and intermolecular vinyl amidation reactions. These accomplishments represent a significant advance in the use of these strategies in the generation of complex molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Interestingly, molecular modelling studies by Shangguan et al (2008) disclosed the thermodynamic stability of isoroquefortine C (1) over roquefortine C. In addition, the absolute configuration of (5aS,10bR,11aS) for 1 was identical to that of the synthetic compound on account of the negative sign of their specific rotations (½a 20 D ¼ 2 300 (c ¼ 0.1, CHCl 3 )) for natural product; lit. : ½a 20 D ¼ 2 409 (c ¼ 0.071, CHCl 3 ) for semisynthetic product (Scott et al 1979); ½a 20 D ¼ 2 329 (c ¼ 0.8, CHCl 3 ) for total synthetic product (Richard et al 2004). Thus, the structure of 1 was determined as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, molecular modelling studies by Shangguan et al (2008) disclosed the thermodynamic stability of isoroquefortine C (1) over roquefortine C. In addition, the absolute configuration of (5aS,10bR,11aS) for 1 was identical to that of the synthetic compound on account of the negative sign of their specific rotations (½a 20 D ¼ 2 300 (c ¼ 0.1, CHCl 3 )) for natural product; lit. : ½a 20 D ¼ 2 409 (c ¼ 0.071, CHCl 3 ) for semisynthetic product (Scott et al 1979); ½a 20 D ¼ 2 329 (c ¼ 0.8, CHCl 3 ) for total synthetic product (Richard et al 2004). Thus, the structure of 1 was determined as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Isoroquefortine C (1), namely, the 3(12)-(Z)-isomer of roquefortine C, has not been reported previously from nature, although it was obtained by photochemical irradiation of roquefortine C (Scott et al 1979). In addition, isoroquefortine C (1) has also been confirmed by chemical synthesis (Schiavi et al 2002;Richard et al 2004). The in vitro antifungal and antibacterial activities of compounds 1 -6 were examined against five phytopathogenic fungi (Gibeberalla saubinetti, Fusarium solani, Botrytis cinerea, Colletotrichum gloeosporioides and Alternaria solani) (Table S1) and four pathogenic bacteria (Escherichia coli, Bacillus subtilis, Bacillus cereus and Staphyloccocus aureus (Table S2) (Li et al 2011;).…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of ROC by LC‐MS/MS comprised quantification of ROC as such, possibly in combination with its stereo‐isomer formed under acidic, basic or photochemical conditions (Richard et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The decision limit was 5 ng ml À1 , while quantification was possible from 10 ng ml À1 injection solution. Quantification of ROC by LC-MS/MS comprised quantification of ROC as such, possibly in combination with its stereo-isomer formed under acidic, basic or photochemical conditions (Richard et al 2004).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…6 We then cleaved the two Boc protecting groups with TMSOTf in DCM as previous reports from total syntheses of HPI natural products indicated that silyl-based Boc-cleavage reagents performed superior than the more usual acid-based deprotections. 21 After basic work-up, we then tested various approaches to regioselectively functionalize the remaining amine derivatization site. The HPI scaffold features two different secondary amines; one of them however is an 'aniline'-type amine which should display lower chemical reactivity and thus allow regioselective variation.…”
Section: Figurementioning
confidence: 99%